Driver, Martha W. and Ray, Sid. eds. 2004: The Medieval Hero on Screen: Representations from Beowulf to Buffy - Gómez Calderón, María José (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen